Evaluating graduate student experiences related to success and resiliency: the influence of mentor relationship, stress, and motivation - Ratajack, Ellen M., author; Graham, Daniel J., advisor; Stallones, Lorann, committee member; Crain, Tori, committee member; Florant, Gregory, committee member (Colorado State University. Libraries, 2020)
Obtaining a graduate degree is a commendable task due to the amount of time and effort required from the individual student. A great deal of past research has examined the undergraduate experience, but few studies focus specifically on the graduate student experience which is drastically different. The following studies both examined the graduate experience with specific focus on the following topics: the importance of resilience and utilizing coping tactics to reduce the impact of stress, discrepancies between actual and ideal mentors, discrepancies between personal goals and program requirements, and finally exploring how graduate students become and stay motivated while earning their degrees.